Cammi Pearson: capstone - Pearson, Cammi, artist (Colorado State University. Libraries, 2014)
The artist's statement: Design has always been inspirational to me, first just in my personal life, and now in a more academic and professional sense. Growing up, I was extremely observational and drawn to details that I would discover and work with later in life. I never really knew what design and graphic design consisted of before my late high-school and early college stage of life. I was hit with the revelation that most everything we see was designed by someone. The giant movie poster looming over your head at the theatre was carefully crafted till it was deemed successful; the pamphlets you would thumb through in the waiting room of your doctor's office; the video game booklet that included characters and descriptions of aspects of the game; all them were designed by someone and I decided that I wanted to be that someone. Design is constantly present in our world, from the natural order of the petals on a flower to a giant banner staring at you with its Helvetica eyes. The world of design, from hand-done type on Polish posters to modern, clean-cut computer generated graphics, is something I am proud to be a part of and proud to learn from. My personal artwork incorporates and often emphasizes illustration and has typography in a supporting role. I enjoy the exploration of traditional media and the manipulation of it through varying vehicles. I am often drawn to bold and flat color that draws a viewer's gaze in and then moves them around the piece. I am eager to exercise my expertise in design and traditional art media. I aspire to continue learning and to discover new concepts in the design world. I am excited to be a part of design and graphic design's continual growth and expansion, and am truly curious as to where it will lead me in the future.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.